Parental expressed emotion and suicidal ideation in adolescents with bipolar disorder. - Ellis, A; Portnoff, L; Axelson, D; Kowatch, R; Walshaw, P; Miklowitz, D (Elsevier, 2014)
Family environmental variables are risk factors for recurrent courses of mood disorder in adolescents. The present study examined the association between parental expressed emotion (EE)-critical, hostile and/or emotionally overinvolved attitudes toward a concurrently ill offspring-and suicidal ideation in adolescents with bipolar disorder. The sample consisted of 95 adolescents with a bipolar I or II diagnosis who had experienced a mood episode in the prior 3 months. Participants (mean age=15.54 years, S.D.=1.4) were interviewed and completed questionnaires regarding current and past suicidal ideation prior to their participation in a treatment trial. Parents completed five-minute speech samples from which levels of EE were assessed. High EE attitudes in parents were associated with current suicidal ideation in adolescents. This relationship was independent of the effects of age, gender, current depressive or manic symptoms, comorbid diagnoses, bipolar I/II subtypes, family adaptability, and family cohesion. These results underscore the importance of addressing the emotional reactivity of caregivers in treating adolescents with bipolar disorder who have suicidal ideation.